Predictive Role of PR Segment, Q Wave Duration and Amplitude, ST Segment, U Wave and Sinus Rhythm in Preeclamptic Pregnant Women in the Third Trimester of Pregnancy - Edebiri O.E; Nwankwo A. A; Akpe P. E; Mbanaso E.L; Obiesi C. N; Chukwu J.A.O (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Early detection and prediction of preeclampsia are crucial to prevent severe complications and ensure timely interventions, Specific ECG patterns, including PR segment, Q wave duration and amplitude, ST segment, U wave, and sinus rhythm were under study for their potential indicators of preeclampsia. This study aims to investigate the predictive role of these ECG patterns in preeclamptic pregnant women in the third trimester of pregnancy. Fourty (40) consenting pregnant women were recruited from St. Philomina Catholic Hospital, Edo State, Nigeria. These subjects consisted of twenty (20) normotensive and twenty (20) preeclamptic pregnant women in their third trimester of pregnancy. After the subjects were identified and recruited into the study, they were taken to the laboratory where their vital signs was taken and their ECG patterns recorded with ECG machine. Data obtained from this study were analysed using Graph Pad Prism 9. Results generated were expressed as mean ± SEM and a P-value of ≤ 0.05 were considered statistically significant. results from this present study show no significant differences were observed in the P-R segment, R-R interval, Q wave duration, Q wave amplitude The study underscores the multifactorial nature of cardiovascular changes in preeclampsia and highlights the potential of ECG parameters in aiding early detection, risk stratification, and management of the condition, despite parameters showing no significant differences. However, PR Segment, Q Wave duration and amplitude, ST Segment , U wave and Sinus rhythm cannot be used to predict preeclampsia